Low‐Cost, Flexible, and Self‐Cleaning 3D Nanocone Anti‐Reflection Films for High‐Efficiency Photovoltaics. (21st January 2014) - Tsui, Kwong‐Hoi; Lin, Qingfeng; Chou, Hungtao; Zhang, Qianpeng; Fu, Huiying; Qi, Pengfei; Fan, Zhiyong
<x xml:space="preserve">Abstract</x> Low‐cost engineered nanotemplates are used to mold flexible nanocone anti‐reflection (AR) films. Both optical reflectance measurements and photovoltaics characterizations demonstrate that the flexible nanocone AR films can considerably suppress device front‐side reflectance and thus improve the power conversion efficiency of high‐efficiency thin‐film CdTe solar cells. Additionally, these nanocone AR films are found to be superhydrophobic and thus possess self‐cleaning capability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>